Welcome to Westonci.ca, where your questions are met with accurate answers from a community of experts and enthusiasts. Join our platform to get reliable answers to your questions from a knowledgeable community of experts. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

2[tex] 3^(x+7) = 9^(x-1)[/tex]

Sagot :

3(x + 7) = 9(x - 1)
3(x) + 3(7) = 9(x) - 9(1)
  3x + 21 = 9x - 9
- 3x          - 3x    
          21 = 3x - 9
        + 9         + 9
         30 = 3x
          3      3
         10 = x